Ideal Student Prototype: A Cognitive Linguistic Study - Rifa’i, Muhamad Husain; Baking, Aad Nur Sayyidus Syuhuur; Wulandari, Betty Ayunda (Universitas Negeri Medan, 2025)
The term “Ideal Student” does not yet have a definition that can accurately describe it. Because of the many human perceptions of how the student can be said to be ideal. The number of categories of each person in expressing the concept of the ideal student itself. So that it creates a diverse prototype in its meaning. This research is based on cognitive linguistic studies. Namely examining a human mind on his speech. This research aims to describe the ideal student prototype in the Ideal Cognitive Model (ICM). This model is able to represent the conceptual knowledge of the ideal speaker without denying other concepts. The researcher provides a commonly spoken concept and respondents will choose according to their cognition of the term ideal student. The data was collected and classified to find the Ideal Meaning in the cognition. Analyzed and classified the type of prototype referring to Lakoff's theory. The results of the analysis are described in the form of tables and explanations of the model. In conclusion, in the ideal student prototype there are three top models in the form of having many soft skills, diligent and active organizations. Keywords: ideal Student; cognitive Linguistics; prototype.